1997
DOI: 10.1161/01.hyp.29.6.1225
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Controlled Biofeedback Blood Pressure Effect in Hypertensive Humans

Abstract: The role of biofeedback in blood pressure control remains ill-defined because of nonspecific (placebo) effects, small study numbers, and the technical limitations of continuous pressure feedback. Clarification of its potential is awaited by those seeking a nonpharmacological approach to blood pressure control. This study examines the capability for systolic pressure lowering of 5 mm Hg or more using continuous pressure feedback in a statistical sample of untreated, well-characterized, mildly hypertensive indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
4
23
0
1
Order By: Relevance
“…Recently, it was reported that the BP-lowering capability of BPBF was independent of the real nature of the feedback signal because placebo biofeedback could also lower BP [35]. Our design does not permit us to exclude the role of non-specific placebo effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the BP-lowering capability of BPBF was independent of the real nature of the feedback signal because placebo biofeedback could also lower BP [35]. Our design does not permit us to exclude the role of non-specific placebo effects.…”
Section: Discussionmentioning
confidence: 99%
“…Blanchard et al (1996) reported that an 8-week thermal biofeedback-training program had no effect on either clinic or ABP measurements. Hunyor et al (1997) found that almost 50% of the hypertensive patients in their study were able to lower their BP in the laboratory using thermal biofeedback. However, the placebo group also lowered their BP to a comparable degree, and the biofeedback sessions had no effect on ABP levels.…”
Section: Biofeedbackmentioning
confidence: 96%
“…These results showed the credible placebo biofeedback intervention to have significant short-time effects on systolic blood pressure, with specific changes in the suggested direction. However, the effects seemed to be restricted to the biofeedback sessions, as arm-cuff blood pressure measurements before and after the sessions as well as 24 h measurements did not change [40].…”
Section: Placebo Effects On Autonomic Functions (A) Cardiovascular Symentioning
confidence: 99%